Experimental Investigation of Bending Behavior of Reinforced Ultra-High-Performance Concrete Decks - Wang, Kangkang; Deng, Kailai; Zhao, Canhui; Wang, Chengzhi (Frontiers in Built Environment, 2019)
Ultra-high-performance Concrete (UHPC) has a wide range of potential civil engineering applications, owing to its excellent mechanical properties and durability. To investigate the bending behavior of reinforced UHPC components, nine reinforced UHPC deck specimens were tested by conducting four-point bending experiments. The crack development, load-carrying capacity, and strain distribution were observed, and the tests results revealed that the introduction of steel fibers into UHPC obviously improved the structure’s toughness and crack resistance. Based on the tests results, a theoretical formula was derived for calculating the bending stiffness of the UHPC decks during the entire loading process, which was divided into three representative stages based on the initial cracking and yielding. The results for the load-deflection response obtained by the formulas are in good agreement with the experimental results.